2011
DOI: 10.25011/cim.v34i5.15673
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of synovial fluid HMGB-1 levels with radiographic severity of knee osteoarthritis

Abstract: Correlation of synovial uid HMGB-1 levels with radiographic severity of knee osteoarthritis Abstract Purpose: is study measured high-mobility group box 1 (HMGB-1) levels in serum and synovial uid (SF) in patients with primary knee osteoarthritis (OA) and correlated these levels with radiographic disease severity.Methods: Seventy-eight OA patients and 30 controls were enrolled in this study. All OA patients were scored according to the Kellgren-Lawrence (KL) grading system. HMGB-1 levels were measured by enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…HMGB‐1 has been demonstrated to be important in the pathogenesis of OA . Previous studies have proved that synovial fluid HMGB‐1 levels were significantly higher in knee OA patients, and were independent factors for radiographic severity of OA . Furthermore, histological grades of OA were proved to be correlated with the HMGB‐1 grade .…”
Section: Discussionmentioning
confidence: 94%
“…HMGB‐1 has been demonstrated to be important in the pathogenesis of OA . Previous studies have proved that synovial fluid HMGB‐1 levels were significantly higher in knee OA patients, and were independent factors for radiographic severity of OA . Furthermore, histological grades of OA were proved to be correlated with the HMGB‐1 grade .…”
Section: Discussionmentioning
confidence: 94%
“…In addition to its roles in acute sterile inflammation, HMGB1 also mediates chronic inflammatory processes (Table ). Specifically, HMGB1 is important in the pathogenesis of rheumatoid diseases . Serum levels of HMGB1 in most of these diseases are significantly higher in comparison with healthy controls and are correlated to the extent of disease activity.…”
Section: Hmgb1 In Chronic Inflammationmentioning
confidence: 99%
“…Serum levels of HMGB1 in most of these diseases are significantly higher in comparison with healthy controls and are correlated to the extent of disease activity. In osteoarthritis, HMGB1 levels are significantly higher in the synovial fluid of patients, and anti‐HMGB1 antibodies inhibit the development of synovial inflammation and joint swelling in experimental models of arthritis . Similarly, biopsy specimens from rheumatoid synovitis reveal aberrant HMGB1 expression associated with joint destruction , whilst injection of HMGB1 into joints can cause long‐lasting destructive arthritis .…”
Section: Hmgb1 In Chronic Inflammationmentioning
confidence: 99%
“…19,[29][30][31] Recent study showed a correlation between synovial fluid levels of HMGB-1 and disease severity of primary knee OA, suggesting the HMGB-1 as a possible OA biomarker prognostic. 32 Considering that OA is an inflammatory disease, the importance of the understanding of the effect of rehabilitation treatment in the systemic inflammatory profile is crucial for rehabilitative treatment.…”
Section: Introductionmentioning
confidence: 99%